Optimized serial expansion of human induced pluripotent stem cells using low‐density inoculation to generate clinically relevant quantities in vertical‐wheel bioreactors. (22nd May 2020) - Borys, Breanna S.; So, Tania; Colter, James; Dang, Tiffany; Roberts, Erin L.; Revay, Tamas; Larijani, Leila; Krawetz, Roman; Lewis, Ian; Argiropoulos, Bob; Rancourt, Derrick E.; Jung, Sunghoon; et al.
Abstract: Human induced pluripotent stem cells (hiPSCs) have generated a great deal of attention owing to their capacity for self‐renewal and differentiation into the three germ layers of the body. Their discovery has facilitated a new era in biomedicine for understanding human development, drug screening, disease modeling, and cell therapy while reducing ethical issues and risks of immune rejection associated with traditional embryonic stem cells. Bioreactor‐based processes have been the method of choice for the efficient expansion and differentiation of stem cells in controlled environments. Current protocols for the expansion of hiPSCs use horizontal impeller, paddle, or rocking wave mixing method bioreactors which require large static cell culture starting populations and achieve only moderate cell fold increases. This study focused on optimizing inoculation, agitation, oxygen, and nutrient availability for the culture of hiPSCs as aggregates in single‐use, low‐shear, vertical‐wheel bioreactors. Under optimized conditions, we achieved an expansion of more than 30‐fold in 6 days using a small starting population of cells and minimal media resources throughout. Importantly, we showed that that this optimized bioreactor expansion protocol could be replicated over four serial passages resulting in a cumulative cell expansion of 1.06E6‐fold in 28 days. Cells from the final day of the serial passage were of high quality, maintaining a normal karyotype, pluripotent marker staining, and the ability to form teratomas in vivo. These findings demonstrate that a vertical‐wheel bioreactor‐based bioprocess can provide optimal conditions for efficient, rapid generation of high‐quality hiPSCs to meet the demands for clinical manufacturing of therapeutic cell products. Abstract : Under optimized conditions in vertical‐wheel bioreactors, we achieved an expansion of human induced pluripotent stem cells of more than 30‐fold in 6 days using a small starting population of cells and minimal media resources throughout. Importantly, we showed that this optimized bioreactor expansion protocol could be replicated over four serial passages resulting in a cumulative cell expansion of 1.06E6‐fold in just 28 days.